English Students' Perception on the Use of Edlink Platform during Covid-19 Pandemic at University - Iffa Luxviya; M. Fadhly Farhy Abbas (LPPM STBA Persada Bunda, 2024)
Online learning is any learning that uses the internet or web-based. Online learning can be done by using learning applications, one of which is the Edlink platform. This research aims at explaining the perception of English education students on the use of Edlink platform during covid-19 pandemic. This research used descriptive-quantitative research methods. The population of the research was the first, third, and fifth semester student in English department in Universitas Lancang Kuning. The researchers selected a sample of 45 students from the population. In the data collection, researchers used questionnaires. Before being handed out the questionnaire tested its validity and reliability values using Correlation Product Moment in SPSS 17.0. There is a questionnaire of 22 statements that valid because of sig results. (2-tailed)]< significant level (Î±) 0,05. With cronbach-alpha >970 the result showed that students' perception of the use of the Edlink platform during the covid-19 pandemic that the majority of English education students have a positive and categorized into high perception of the use of the Edlink platform application. Before this application is used students are given socialization and application coordinators to deal with the obstacles experienced. In conclusion students can adapt the Edlink platform to temporarily replace learning during covid-19.